Enhancing Behavioral Health Services for Child Welfare-Involved Parents: A Qualitative Study. Issue 5 (20th October 2022) - Boel-Studt, Shamra M.; Flynn, Heather A.; Deichen Hansen, Megan E.; Panisch, Lisa S.
ABSTRACT: Behavioral health issues are prevalent among child welfare-involved parents. Despite associations with parenting challenges and maltreatment, parents' behavioral health conditions often go untreated. In this study, we explore challenges with addressing behavioral health needs of parents involved in the child welfare system. Focus groups with child welfare and behavioral health providers were conducted to explore gaps and opportunities to enhance behavioral health care for child-welfare involved parents. Three themes were identified: parental motivation and buy-in, behavioral health assessments and screenings, and communication and service coordination. Implications for policy and practice include increased training on measurement-based care and effective cross-system collaboration.